2011
DOI: 10.1029/2011je003847
|View full text |Cite
|
Sign up to set email alerts
|

Observations of thermal tides in the middle atmosphere of Mars by the SPICAM instrument

Abstract: [1] We use vertical profiles of Martian atmospheric density, pressure, and temperature from the Mars Express SPICAM UV spectrometer to study thermal tides in the poorly studied middle atmosphere region at 70-120 km. Here we show that nonmigrating tides cause zonal pressure variations of tens of percent and zonal temperature variations on the order of 10 K in these observations. Wave-2 and wave-3 components are dominant, consistent with previous work at lower and higher altitudes and with theoretical prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 51 publications
(135 reference statements)
6
52
0
Order By: Relevance
“…Comparing the density with temperature, their variation patterns are very similar but appear to be out of phase, specifically for wave 2 and wave 3 components. This indicates that the temperature variation is due to the adiabatic cooling/warming caused by tides as discussed by Withers et al [].…”
Section: Longitudinal Structuressupporting
confidence: 89%
See 4 more Smart Citations
“…Comparing the density with temperature, their variation patterns are very similar but appear to be out of phase, specifically for wave 2 and wave 3 components. This indicates that the temperature variation is due to the adiabatic cooling/warming caused by tides as discussed by Withers et al [].…”
Section: Longitudinal Structuressupporting
confidence: 89%
“…Withers et al [] have found that both wave 2 and wave 3 can dominate the longitudinal structures at 70–120 km altitudes, and the wave amplitudes change dramatically with altitude. Our observations are for higher altitudes, but similar features are seen.…”
Section: Longitudinal Structuresmentioning
confidence: 64%
See 3 more Smart Citations